2004
DOI: 10.1002/dvdy.20243
|View full text |Cite
|
Sign up to set email alerts
|

FGF‐2 signaling is sufficient to induce dermal condensations during feather development

Abstract: In a previous report, we showed that fibroblast growth factor-2 (FGF-2) is a signal produced by epidermal placode cells during feather development and that this growth factor can induce feathers in scaleless mutant skins that fail to form feathers due to a defective epidermis (Song et al., [1996] Proc Natl Acad Sci USA 93:10246 -10249). Here, we test whether FGF-2 is sufficient to induce dermal condensations, structures that normally form under the control of signals from the epidermal placode and are identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(48 citation statements)
references
References 96 publications
1
46
0
Order By: Relevance
“…These results are in agreement with the proposed integration of the Shh-and Bmpmediated signaling pathways in the morphogenesis (Nohno et al, 1995;Noramly and Morgan, 1998;Harris et al, 2002) and spacing (Noramly and Morgan, 1998;Bardot et al, 2004) of the placodes during feather and scale development. Similarly, Fgf signaling has been implicated in the patterning of feathers (Mandler and Neubüser, 2004;Song et al, 2004;Wells et al, 2012), and we have previously shown Fgf8 and Fgf10 to be expressed in the developing carapace of T. scripta (Loredo et al, 2001; Cebra-Thomas et al, 2005). Fig.…”
Section: Discussionsupporting
confidence: 59%
“…These results are in agreement with the proposed integration of the Shh-and Bmpmediated signaling pathways in the morphogenesis (Nohno et al, 1995;Noramly and Morgan, 1998;Harris et al, 2002) and spacing (Noramly and Morgan, 1998;Bardot et al, 2004) of the placodes during feather and scale development. Similarly, Fgf signaling has been implicated in the patterning of feathers (Mandler and Neubüser, 2004;Song et al, 2004;Wells et al, 2012), and we have previously shown Fgf8 and Fgf10 to be expressed in the developing carapace of T. scripta (Loredo et al, 2001; Cebra-Thomas et al, 2005). Fig.…”
Section: Discussionsupporting
confidence: 59%
“…Such results are consistent with those from previous quail-duck transplants, where quail donor neural crest cells were shown to govern beak morphology by executing autonomous molecular programs and by regulating gene expression in the mesenchyme and epithelia of the developing facial primordia (Schneider and Helms, 2003). Beyond the molecules examined here, we predict that other genes, including members and targets of the FGF, Epidermal Growth Factor and Wnt pathways, which play a role during feather morphogenesis (Noji et al, 1993;Tanda et al, 1995;Widelitz et al, 1996;Noramly et al, 1999;Widelitz et al, 1999;Olivera-Martinez et al, 2001;Tao et al, 2002;Atit et al, 2003;Chodankar et al, 2003;Chang et al, 2004;Mandler and Neubuser, 2004;Rouzankina et al, 2004;Song et al, 2004), would be differentially regulated by donor neural crest. In the future, combining our chimeric approach with more quantitative and comprehensive methods of gene expression analysis, such as microarrays, could yield new candidate molecules that underlie feather morphogenesis.…”
Section: Neural Crest Regulates Expression Of Genes Essential To Featmentioning
confidence: 74%
“…Although the identity of the first dermal signal is not known, likely candidates include molecules in the Bone Morphogenetic Protein (BMP) and Fibroblast Growth Factor (FGF) families (Tao et al, 2002;Pispa and Thesleff, 2003;Mandler and Neubuser, 2004). A decade of molecular research on feather morphogenesis suggests that a general hierarchical sequence of signaling events may be from the BMP and FGF pathways, to the Sonic Hedgehog (SHH) and Wnt pathways, to the Delta/Notch pathway, to numerous transcription factors and structural genes (Chuong et al, 2001;Song et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…First, we used the basic medium with or without 10% Fetal Bovine Serum (FBS), which has a known chemoattractant effect. Secondly, we added FGF2, which is known to have a positive chemoattractant effect on dermal cells (Song et al, 2004), to the basic media with or without FBS. Each experiment, done in triplicate, was measured relative to the cell migration obtained with the basic medium containing FBS (100%).…”
Section: Bmp2 and Bmp7 Have Opposite Effects On Dermal Fibroblast Migmentioning
confidence: 99%
“…The different signals have been classified as activators or inhibitors (Jung et al, 1998). The FGF pathway acts as an activator, and its epidermal expression promotes dermal condensation formation via its chemoattractant effect on fibroblasts (Song et al, 1996;Song et al, 2004;Viallet et al, 1998). To date, BMPs have generally been considered to be inhibitors of feather formation, and three members are expressed in the primordium domain: BMP2, BMP4 and BMP7, where BMP2 and BMP4 belong to the same subgroup (Miyazono et al, 2005).…”
Section: Introductionmentioning
confidence: 99%